SISTEM LEGALISASI PERKAWINAN MELALUI PENDEKATAN PERADILAN KELUARGA TERPADU( INTEGRETED FAMILY COURT ) BERBASIS MASYARAKAT PEDESAAN - yuyun yulianah; Cucu Solihah; Mumuh M. Rozi (JURNAL HUKUM DE'RECHTSSTAAT, 2020)
The rise of sirri marriage or underhanded (without involving state law) and the lack of public knowledge of the law supported by the powerlessness and inability to access and act before the law as a result of geographical location and the low level of public education gave birth to the legal consequences of marital legality demands which would be used as marriages the legal basis for civil relations, for that we need a model of marriage legalization through an integrated community court approach based on rural communities. The aim is to provide solutions to the legal requirements of marriage law for rural communities and are unable to research methods using doctrinal and nondoctrinal legal methods. The data used are primary data and secondary data. Secondary data consists of primary, secondary and tertiary legal material. Data collection techniques include observation, in-depth interviews, focus group discussions, questionnaire distribution, and literature study. Data analysis techniques using qualitative normative analysis methods and interactive analysis models. The results and conclusions show that rural communities with limited health insurance seeking justice, economics and science are in dire need of protection and law from Sirri or under-hand marriages for civil purposes.